The effects of islamic microfinance on borrowers household income and wellbeing in Bangladesh: religiosity as moderator - Ahamad, Shamsuddin author (School of Business Innovation & Technopreneurship, 2017)
The general objective of this research is to measure the effects of Islamic microfinance on borrowers' household Income and welfare. The specific objectives are as follows; to examine the effects of Islamic microfinance on borrowers' household income; to examine the effects of Islamic microfinance on borrowers household wellbeing; to Identify the factors that affected to the income and wellbeing; to assess the moderating effects of religiosity on the relationship between influencing factors and borrower's income; to assess the moderating effects of religiosity on the relationship between influencing factors and borrower's wellbeing.